WASTE PICKERS' WORK: STIGMA AND UTILITY - Petružytė, Donata (Socialinė teorija, empirija, politika ir praktika, 2009)
The aim of this paper is to establish common traits of work of waste pickers. Analysis is based on comparison of data of ethnographic research conducted in Lithuanian dumps and research results presented in various scientific publications representing situation in various countries. In this paper we discuss the work of waste pickers concerning three aspects: (1) common characteristics work of waste pickers; (2) waste pickers self-perception and attitude of society towards waste pickers and their work; (3) benefits of waste pickers work. The paper is divided in three chapters according to these topics.
Keywords: Waste pickers; Work; Public attitude; Lithuanian dumps